Protecting women's health in a changing climate: The role of community-based adaptation - Emma Duus; Doreen Montag (Elsevier, 2022)
Introduction: Community-based adaptation is an emerging approach to mitigating the health consequences of climate change, yet, the interactions amongst climate change, community-based adaptation, health and gender have not been explored as a single nexus in a low-income setting. The paper uses the Adaptation Learning Programme as a case to explore this nexus. The Adaptation Learning Programme was a gender-integrated community-based adaptation programme implemented from 2010 to 2015 in Garissa County in Kenya. Methods: A case study methodology with an interpretivist epistemological approach was chosen to explore the complexity underlying the unique context of the Adaptation Learning Programme's implementation in Garissa. Data was collected from grey literature published and was analysed using a systematic framework. Results: Adaptation Learning Programme community-based adaptation interventions enhanced adaptive capacity, through enhancing women's access to markets and economic assets, teaching women adaptive agricultural practices, including women in decision-making processes, and disseminating gender-sensitive climate information to communities. These processes mitigated several climate-related health risks faced by women in Garissa, but also failed to address the structural causes of their health vulnerabilities. The findings can be scaled up to inform further community-based adaptations and national policies on gender-sensitive approaches to climate change.